INCLUSIVE HOUSING POLICY AS A TOOL FOR INCREASING POPULATION ACCESS TO SOCIAL HOUSING - SEMENOV, Nazar (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the role of inclusive housing policy as a tool for providing social housing to Ukraine’s population, with an emphasis on the period of full-scale war and its consequences. The primary outcome of this work is the development of methodological principles for creating an inclusive housing policy, informed by an analysis of the scientific and theoretical aspects of social housing, as well as its legal, economic, and social characteristics. The primary issue in modern housing provision in Ukraine is the acute shortage of affordable housing, resulting from the destruction of infrastructure, mass population displacement, outdated housing stock, and uneven resource allocation. Equal and fair access to social housing is a key mechanism for social protection of the population. The article presents a brief overview of domestic and international experience in defining the essence of social housing, reveals the differences between the concepts of "social housing" and "affordable housing", as well as the criteria for providing such housing (income, IDP status, social needs). The study’s results suggest additional principles for inclusive housing policy that further improve the regulatory, legal, and organizational provision of social housing to the population. Among these are the principles of decommercialization, public control, quality and standards, sustainability, environmental friendliness, decommodification, and protection of tenants’ rights. The need to achieve a balance of interests among all stakeholders is substantiated, including the state, beneficiaries (IDPs, orphans, and low-income families), service providers, and the public. The connection between social housing and sustainable development, social integration, and the realization of human rights (in accordance with the UN’s 2030 Goals) is emphasized. An inclusive housing policy based on the proposed principles will contribute to overcoming the housing crisis, reducing poverty, and achieving social stability. Areas of further research will include the development of mechanisms for inclusive social housing provision in Ukraine, considering the country’s specific modern development and leading European experiences.